The dopamine trap: Effects of short-form video (SFV) addiction on mental health - Ahmed, Muaz; Shafi, Syeda Ramsha (Journal of the Pakistan Medical Association, 2026)
Dear editor, With the surge in technological advances and the aftershocks of the COVID-19 pandemic, platforms like TikTok, Instagram Reels, and YouTube Shorts have become an integral part of our daily lives, especially among children and adolescents. These videos, typically lasting no longer than 30 seconds, provide instant entertainment and gratification but at a cost that is often overlooked. Short-form videos (SFV) became a popular coping mechanism for loneliness, stress, and anxiety, especially post-COVID with the need for isolation, offering users a sense of community, entertainment, inspiration and even education. These platforms provided a temporary escape from the challenges of daily life, allowing individuals to pass time and, in some cases, enhance their life satisfaction (1). However, as consumption increased, the initial benefits began to fade, and what started as a means of relief to mitigate stress gradually transformed into an addiction. Over time, this shift led to negative consequences, including a decline in attention span, emotional regulation, and overall mental well-being. The constant bombardment of rapid information, curated by algorithms, creates a paradoxical paradise that may dull cognitive functioning, as outlined by Cognitive Load Theory [2]. This overstimulation has been associated with attention deficits, which serve as mediators for memory impairment, decreased self-control, and delayed responsiveness to external stimuli, which can be partly explained by the dopamine addiction model, where the constant rewards from these videos create a never-ending pattern of craving, overstimulation, and emotional numbness [3]. Adolescents appear especially vulnerable. Studies link excessive short-form video use to academic procrastination, poor sleep quality, weakened impulse control, and academic burnout [4]. Physical health also suffers, with increased cases of poor vision and reduced physical fitness due to prolonged screen exposure and sedentary lifestyle. Alarmingly, these compounded effects have been linked to rising rates of suicidal ideation [5]. One possible explanation is that overstimulation and shallow pleasures create a sense of emotional numbness and loss of meaning—what Nietzsche termed passive nihilism, a state where individuals no longer find life worth engaging with. We urge the academic and medical community to recognize the growing threat posed by excessive short-form video (SFV) consumption. We propose that healthcare providers, particularly paediatricians and general practitioners, consider including brief screening questions about social media and SFV consumption patterns during routine adolescent mental health assessments.